Professores de música em (trans)formação: um estudo sobre concepções e práticas constituindo o habitus docente - Ramalho, Luisiane Frota Correia Lima (2023)
This research investigated the relations between the constitution of educational habitus of the music teachers in the municipal network of Fortaleza and their conceptions and pedagogical practices. We highlight as specific objectives of this investigation: to analyze the relations between academic (curricular) training and the constitution of the educational habitus; to verify the repercussion of the pedagogical-musical conceptions and practices in the choices of musical repertoires and didactic materials; to observe and describe the formative experiences as constituents of the educational habitus based on the teachers’ trajectory. With the qualitative conjuncture of a multireference theoreticalmethodological framework, the theoretical arguments are based on the praxeology by Pierre Bourdieu (1996, 2011, 2017), on the life and training stories of authors such as António Nóvoa (2014) and Marie Christine Josso (2002), and on the curricular perspective of Miguel Arroyo (2011); Michael Apple (2006) and Sousa Santos (1996). The research used methodological tools such as the application of a questionnaire and individual interviews with the social agents in question, the music/art teachers in the municipal network of Fortaleza. The data provided, the information and the statements comprise these teachers’ experiences of socialization and training with the reports about their teaching trajectories and integrate oral and written narratives from ten teachers. Four categories of analysis were established, the knowledge from family formation, school education, teachers’ academic education and their teacher training. Data analysis centered on the theoretical framework in question enabled the conclusion that the constitution of the educational habitus traverses different types of knowledge, be them acquired through family, school or academic curricula, as well as those arising from the diverse musical experiences, including those acquired in teaching practice, constituting the incorporated past. The result of this investigation reveals the conditions of the field of action of the agents involved in the structured space in which the musical education in the municipal network of Fortaleza is situated. The research on the teaching trajectory gave voice to the agents, with the reports of lived experiences, unveiling the meanings of constituted dispositions and confirming the thesis that the conceptions and practices constitute the habitus arising from the formative knowledge and the school environment.